Bio-based super-hydrophobic composite coating, preparation method and application

The modification of silica by silicone-modified castor oil-based polyurethane and oleic silane coupling agent is made to construct a bio-based superhydrophobic composite coating, which solves the problem of insufficient stability of the bio-based superhydrophobic coating. It achieves high stability and widely applicable superhydrophobic performance, suitable for a variety of application scenarios.

CN119242150APending Publication Date: 2025-01-03HUBEI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456986.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The bio-based superhydrophobic coating has poor stability and is easily lost, resulting in insufficient hydrophobicity in applications.

Method used

Silicon dioxide is modified using castor oil-based polyurethane hybrid solution and oleic acid-based silane coupling agent, and superhydrophobic composite coating is constructed on the surface of the substrate by spraying, using silicone and oil The covalent bonding of acid silanes forms stable nanostructures, reducing material surface energy and enhancing hydrophobicity.

Benefits of technology

It realizes the high stability and wide applicability of bio-based superhydrophobic composite coating, can maintain superhydrophobic properties on different substrates, is wear-resistant, weather-resistant and stain-resistant, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242150A_ABST
    Figure CN119242150A_ABST
Patent Text Reader

Abstract

The invention discloses a bio-based super-hydrophobic composite coating as well as a preparation method and application thereof. According to the preparation method of the bio-based super-hydrophobic composite coating, siloxane-modified castor oil-based polyurethane and oleic acid-based silane coupling agent modified nano silicon dioxide are alternately sprayed to prepare a super-hydrophobic surface layer, silicon dioxide constructs a rough structure on the surface of a material, and long-chain carbon of oleic acid silane is used for reducing surface free energy of the material; siloxane modified bio-based polyurethane is used for bonding a base material and silicon dioxide, and under the synergistic effect of siloxane modified bio-based polyurethane, the base material and silicon dioxide, stable super-hydrophobicity of the material surface is achieved. Compared with a technology based on hydrogen bonds, molecular chain winding or esterification reaction in the prior art, the prepared super-hydrophobic composite coating is higher in robustness, suitable for being applied to the surface of any base material, easy to expand and convenient to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of super-hydrophobic coatings, and in particular to a bio-based super-hydrophobic composite coating, a preparation method and an application thereof. Background Art

[0002] Superhydrophobic materials are a special type of surface treatment material. They have extremely high water contact angles (usually greater than 150°) and low rolling angles (usually less than 10°), which allows water droplets to form a nearly perfect sphere on the surface of the material and easily roll away impurities such as dust, thereby achieving a self-cleaning effect. In recent years, the development of superhydrophobic materials has attracted widespread attention, and they have shown great application potential in anti-fouling self-cleaning, oil spill treatment, protective coatings, self-healing materials, and sensors. The superhydrophobic properties of superhydrophobic materials are closely related to the roughness and surface energy of the material surface. Superhydrophobic materials usually have a surface roughness structure at the micron or nanometer level. When a droplet contacts this rough surface, the actual contact area is reduced, resulting in a decrease in surface energy; the lower the surface energy of the material, the lower its affinity for water, which can enhance the hydrophobicity of the material.

[0003] Etching, sol-gel, vapor deposition and femtosecond laser are the main methods for regulating the surface roughness of super-hydrophobic materials. These methods are time-consuming, labor-intensive, complicated and costly and cannot be widely promoted. In terms of low surface energy materials, fluorinated compounds, such as polytetrafluoroethylene (PTFE) and fluorinated polymers, are one of the most commonly used super-hydrophobic materials with low surface energy and have good hydrophobic properties. However, the use of such materials to make hydrophobic coatings has been proven to cause serious harm to the health of organisms and the sustainable development of the ecology.

[0004] Bio-based super-hydrophobic coating is a special surface treatment material made from bio-based materials. It has an extremely high water contact angle and a low rolling angle, which can make water droplets form a nearly perfect sphere on the surface and easily roll away impurities such as dust, thereby achieving a self-cleaning effect. Natural long-chain fatty acids are ideal for developing stable super-hydrophobic materials because they not only have excellent biocompatibility and environmental friendliness, but also can effectively reduce the surface energy of the material surface, thereby enhancing its hydrophobicity. At present, most natural long-chain fatty acids derived from biomass are coated on the surface of the material by "dip coating". Fatty acids and materials can only be combined based on hydrogen bonds or molecular chain entanglement, resulting in weak stability, which is manifested as the problem of easy loss of bio-based super-hydrophobic coatings.

[0005] Therefore, it is urgent to develop a preparation process for a highly stable bio-based super-hydrophobic coating to solve current technical problems. Summary of the invention

[0006] In view of this, the purpose of the present application is to provide a bio-based super-hydrophobic composite coating, a preparation method and an application, so as to solve the technical problem that the bio-based super-hydrophobic coating in the prior art is not stable and is easy to lose.

[0007] To achieve the above objectives, this application provides the following technical solutions:

[0008] In a first aspect, the present application provides a method for preparing a bio-based super-hydrophobic composite coating, which comprises the following steps:

[0009] S1. Preparation of siloxane-modified castor oil-based polyurethane hybrid solution;

[0010] S2. Synthetic oleic acid silane coupling agent;

[0011] S3. The silica was modified with the oleic silane coupling agent obtained in S2 to obtain super-hydrophobic modified silica, and the super-hydrophobic modified silica was added to isopropanol to obtain a super-hydrophobic modified silica solution;

[0012] S4. Spraying a siloxane-modified castor oil-based polyurethane hybrid solution and a super-hydrophobic modified silica solution on the surface of the substrate in sequence, and obtaining the bio-based super-hydrophobic composite coating after curing.

[0013] In a second aspect, the present application provides a bio-based super-hydrophobic composite coating, which is prepared by the aforementioned preparation method.

[0014] In a third aspect, the present application provides the use of the aforementioned bio-based super-hydrophobic composite coating in the preparation of super-hydrophobic materials and products.

[0015] The bio-based super-hydrophobic composite coating, preparation method and application provided in this application have at least the following beneficial effects compared with the prior art:

[0016] 1. In the preparation method of the bio-based super-hydrophobic composite coating provided in the present application, a new coupling agent (oleic acid siloxane) is synthesized, which loads long-chain bio-based long-chain alkanes on the surface of silica based on silanol condensation to obtain a green, low-surface-energy nanomaterial.

[0017] 2. In the preparation method of the bio-based super-hydrophobic composite coating provided in the present application, a castor oil-based polyurethane with siloxane side groups and terminated by siloxane is synthesized to provide a large number of silicon-oxygen bonds that can covalently bond with nanomaterials.

[0018] 3. In the preparation method of the bio-based super-hydrophobic composite coating provided by the present application, the super-hydrophobic surface layer is prepared by alternately spraying siloxane-modified castor oil-based polyurethane and oleic acid silane coupling agent modified nano-silicon dioxide, and silicon dioxide builds a rough structure on the material surface, and the long-chain carbon of oleic acid silane is used to reduce the surface free energy of the material, and the bio-based polyurethane modified by siloxane is used to bond the substrate and silicon dioxide. Under the synergistic effect of the three, the robust super-hydrophobicity of the material surface is achieved. Compared with the prior art by the technology based on hydrogen bonding, molecular chain winding or esterification reaction, the robustness of the super-hydrophobic composite coating prepared by the present application is stronger, suitable for application to any substrate surface, easy to expand, and convenient to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The 1H-NMR spectrum provided in the examples of the present application, wherein (a) is the 1H-NMR spectrum of castor oil, and (b) is the 1H-NMR spectrum of silylated castor oil.

[0020] Figure 2 The 1H-NMR spectra of oleic acid and oleosilane provided in the examples of the present application, wherein (a) is the 1H-NMR spectrum of oleic acid, and (b) is the 1H-NMR spectrum of oleosilane.

[0021] Figure 3 This is a diagram of the preparation process of the SOA@SiO2 / SCPU bio-based composite coating provided in an embodiment of the present application.

[0022] Figure 4 The mechanical properties test results of the SOA@SiO2 / SCPU bio-based composite coating provided in the embodiments of the present application, wherein (a) is the sandpaper wear test result under a 200g weight, (b) is the finger touch test result, and (c) is the water drop impact test result.

[0023] Figure 5 The chemical stability test results of the SOA@SiO2 / SCPU bio-based composite coating provided in the embodiments of the present application, wherein (a) is the effect of different solvents on the water contact angle of the coating; (b) is the effect of different pH values ​​on the water contact angle of the coating.

[0024] Figure 6 The weather resistance test results of the SOA@SiO2 / SCPU bio-based composite coating provided in the embodiments of the present application, wherein (a) is the change of the water contact angle of the coating after being treated under different conditions over time, and (b) is the change of the water contact angle of the coating after being treated at different temperatures.

[0025] Figure 7The results of the diversity of super-hydrophobic properties of the SOA@SiO2 / SCPU bio-based composite coating provided in the embodiments of the present application; wherein, (a) is the hydrophobic state of different types of liquids (soy sauce, vinegar, wine, juice, ink, coffee, milk, tea) on different substrates without coating (left) and with coating (right); (b) is the contact angle of different types of liquids (soy sauce, vinegar, wine, juice, ink, coffee, milk, tea) on different substrates.

[0026] Figure 8 Schematic diagram of the anti-fouling performance test of the SOA@SiO2 / SCPU bio-based composite coating provided in the embodiment of the present application, wherein (a) is a schematic diagram of the immersion-removal cycle test in a graphite solution; (b) is a schematic diagram of the wind blowing decontamination test; and (c) is a schematic diagram of the water drop rolling decontamination test. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0028] Those skilled in the art will appreciate that, unless otherwise stated, the words "said", "the", "the aforementioned", and "above" used in the text of the present application may also include plural forms. It should be further understood that the wording "comprising" used in the specification of the present application means the presence of the features, steps, and operations, but does not exclude the presence or addition of one or more other features, integers, and steps.

[0029] In the text of this application, the terms "first", "second" and the like are used to distinguish between identical or similar items with substantially the same functions and effects. This is only for the purpose of clearly describing the technical solutions of the embodiments of this application, and shall not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0030] Those skilled in the art will appreciate that, in the examples of the present application, if no specific conditions are specified, the experiments are carried out under conventional conditions or conditions recommended by the manufacturer, and the reagents or instruments used, if no manufacturer is specified, are conventional products that can be purchased commercially.

[0031] In order to solve the problem of poor stability of the bio-based super-hydrophobic coating prepared in the prior art, the embodiment of the present application selects oleic acid, a natural fatty acid with eighteen carbons and one double bond, as a bio-based hydrophobic compound, and uses a thiol-ene click chemistry reaction to silylate the oleic acid to synthesize a new oleic acid-based silane coupling agent, and then uses the silicon hydroxyl bond to generate a strong covalent bond Si-O-Si with the hydroxyl group on the surface of silica, thereby obtaining super-hydrophobic modified silica particles, thereby achieving the purpose of grafting long chains of natural fatty acids on the surface of silica, giving it a robust super-hydrophobic property, and avoiding the disadvantage of weak super-hydrophobic stability caused by modification methods such as "dip coating"; finally, by using a spraying method, by regulating the spraying ratio and spraying interval time of super-hydrophobic particles and siloxane-modified castor oil-based polyurethane, a novel bio-based polyurethane composite coating with robust super-hydrophobic performance is obtained.

[0032] Based on this, an embodiment of the present application provides a method for preparing a bio-based super-hydrophobic composite coating, which includes the following steps: S1. preparing a siloxane-modified castor oil-based polyurethane hybrid solution (SCPU); S2. synthesizing an oleic acid-based silane coupling agent; S3. modifying silica with the oleic acid-based silane coupling agent obtained in S2 to obtain super-hydrophobic modified silica, and adding the super-hydrophobic modified silica to isopropanol to obtain a super-hydrophobic modified silica solution; S4. spraying the siloxane-modified castor oil-based polyurethane hybrid solution and the super-hydrophobic modified silica solution on the surface of the substrate in sequence, and obtaining the bio-based super-hydrophobic composite coating after curing.

[0033] In certain embodiments, in the above step S1, the specific preparation method of the siloxane-modified castor oil-based polyurethane hybrid solution (SCPU) is as follows: (1) adding castor oil (CO), mercaptopropyl trimethoxysilane and an appropriate amount of photoinitiator into a sample bottle filled with an inert gas to obtain a first mixture; (2) placing the sample bottle containing the first mixture under ultraviolet light for reaction overnight to obtain silanized castor oil (SCO) (structure as shown in FIG. Figure 1 (3) adding isophorone diisocyanate and castor oil to the sample bottle and heating the sample bottle under the protection of inert gas for reaction; (4) adding polycaprolactone to the sample bottle for chain extension reaction to obtain -NCO terminated castor oil-based polyurethane; (5) adding mercaptopropyl trimethoxysilane after cooling and reacting for a period of time to obtain a uniform and transparent siloxane-modified castor oil-based polyurethane hybrid solution (SCPU).

[0034] In certain embodiments, in steps (1) and (3), the inert gas is argon.

[0035] In certain preferred embodiments, in step (1), the photoinitiator is dimethyl benzoate, and its mass proportion in the first mixture is 1% to 4%.

[0036] In some embodiments, in step (2), the wavelength of the ultraviolet light is 300-400 nm, and the light intensity is 1200-1500 mW.

[0037] In certain embodiments, in step (3), the heating reaction temperature is 60-75° C., and the reaction time is 4-6 h.

[0038] In certain embodiments, in step (5), the temperature after cooling is 35-45°C.

[0039] In some embodiments, the specific steps of synthesizing the oleic acid-based silane coupling agent (SOA) in step S2 are as follows: oleic acid (chemical structure is as follows: As shown), 3-mercaptopropylethoxysilane (chemical structure is as follows: As shown), a photoinitiator is mixed to form a second mixture, and the second mixture is reacted under ultraviolet light to synthesize an oleic acid-based silane coupling agent (chemical structure is as follows: shown), Figure 2 1H-NMR is the hydrogen nuclear magnetic resonance spectrum (1H-NMR) of oleic acid and oleylsilane.

[0040] In some preferred embodiments, in the above step S2, the wavelength of the ultraviolet light is 300-400 nm, the light intensity is 1200-1500 mW, and the irradiation time is 20-24 h.

[0041] In some embodiments, in the above step S2, the photoinitiator is dimethyl benzoate, and its mass proportion in the second mixture is 1% to 4%.

[0042] In some embodiments, in the above step S3, the specific steps of modifying silica with an oleic acid silane coupling agent are: mixing silica, anhydrous ethanol, and deionized water, adjusting the pH value of the mixed solution to 8.5-9.5, further ultrasonically treating, adding an oleic acid silane coupling agent (SOA), mixing evenly, drying, washing with alcohol, and drying again to obtain super hydrophobic modified silica particles.

[0043] In some embodiments, in the above step S4, the material of the substrate is at least one of glass, metal, wood, concrete, and textile.

[0044] Based on this, an embodiment of the present application also provides a bio-based super-hydrophobic composite coating, which is prepared by the aforementioned preparation method.

[0045] Based on this, the embodiments of the present application also provide the application of the aforementioned bio-based super-hydrophobic composite coating in the preparation of super-hydrophobic materials and products.

[0046] The application of bio-based super-hydrophobic composite coatings is very wide. In some application embodiments, bio-based super-hydrophobic composite coatings can be used on building surfaces, car shells, solar panels, etc., so that water droplets carry away dust and other impurities when rolling on the surface, thereby reducing the need for cleaning.

[0047] In some application embodiments, by coating the bio-based super-hydrophobic composite coating on the metal surface, it is possible to effectively prevent the contact of moisture and corrosive substances and extend the service life of the material. In some application embodiments, the simple bio-based super-hydrophobic composite coating can be used for oil-water separation equipment, and by utilizing the wettability difference between water and oil, efficient oil-water separation is achieved. In some application embodiments, the bio-based super-hydrophobic composite coating can be used on the surface of equipment such as aircraft and wind turbines to prevent ice accumulation and improve safety and efficiency. In some application embodiments, the bio-based super-hydrophobic composite coating can be applied to the sensor surface to prevent water vapor condensation and improve the accuracy and stability of the sensor. In some application embodiments, in a microfluidic system, the bio-based super-hydrophobic composite coating can be used to control the flow of fluid and prevent cross contamination. In some application embodiments, the bio-based super-hydrophobic composite coating is applied in textile and footwear materials, and waterproof and anti-fouling functions can be provided. In some application embodiments, the outer surface of a car, a windshield, a rearview mirror, etc. use the bio-based super-hydrophobic composite coating to reduce the attachment of water droplets and improve driving safety and comfort. In some application embodiments, the use of the bio-based super-hydrophobic composite coating on building surfaces can reduce moisture-induced damage, such as erosion and freeze-thaw damage. In some application embodiments, the use of the bio-based super-hydrophobic composite coating on medical equipment can reduce the adhesion of bacteria and viruses and reduce the risk of hospital infection. In some application embodiments, the use of the bio-based super-hydrophobic composite coating on devices such as smartphones and tablets can provide additional waterproof protection.

[0048] The technical solution of the present application and the technical effects achieved are described in detail below through more specific embodiments.

[0049] Example

[0050] This embodiment provides a method for preparing a bio-based super-hydrophobic composite coating, and the specific steps are as follows:

[0051] (1) Preparation of siloxane-modified castor oil-based polyurethane hybrid solution (SCPU): First, 3.08 g of castor oil (CO), 1.96 g of mercaptopropyl trimethoxysilane and 0.16 g of benzoin dimethyl ether (photoinitiator) were added to a sample bottle filled with argon in sequence, and the mixture was irradiated under an ultraviolet lamp (365 nm, 1400 mW) for 24 h to react. After overnight, silanized castor oil (SCO) was obtained. Then, 8 g of isophorone diisocyanate and 12.41 g of castor oil were added to the bottle. Under argon protection, the mixture was heated to 40 ℃ and then heated to 30 ℃. and 75° C. for 4 to 6 hours until the remaining isocyanate groups reach the theoretical value (based on di-n-butylamine titration); again, 11 g of polycaprolactone (Mw=1000 g / mol) is added to the bottle for chain extension reaction until the remaining isocyanate groups reach the theoretical value to obtain -NCO-terminated castor oil-based polyurethane; finally, by consuming the remaining isocyanate groups with 0.98 g of mercaptopropyltrimethoxysilane at 40° C., a uniform and transparent siloxane-modified castor oil-based polyurethane hybrid solution (SCPU) is obtained;

[0052] (2) Synthesis of oleic acid silane coupling agent (SOA): 28.247 g of oleic acid, 19.634 g of 3-mercaptopropylethoxysilane and 1.56 g of benzoin dimethyl ether (photoinitiator) were weighed and mixed, and then irradiated under ultraviolet light (365 nm, 1400 mW) for 24 h to synthesize oleic acid silane coupling agent (SOA);

[0053] (3) Preparation of oleic acid silane modified silica (SOA@SiO2): 5 g silica, 100 mL anhydrous ethanol, and 1 mL deionized water were added to a beaker, and ammonia water was added to adjust the pH value of the mixed solution to 9.0. The mixed solution was placed in an ultrasonic cell crusher for ultrasonic treatment (650 W, 30 min). After mixing evenly, 4.5 g oleic acid silane coupling agent was added, and the mixture was stirred at 60°C for 12 h and then dried in an oven at 80°C. The dried product was washed with alcohol three times and dried to obtain super hydrophobic modified silica (SOA@SiO2) particles.

[0054] (4) Preparation of SOA@SiO2 / SCPU bio-based composite coating: Figure 3 As shown, at a height of about 10 cm from the glass substrate, press the spray gun to spray 3 ml of SCPU solution on the surface of the substrate, and place the sample in a constant temperature and humidity test box (humidity 35%, temperature 37°C). After the polymer reaches a semi-cured state (curing time 160 min), 3 mL of SOA@SiO2 isopropanol solution is sprayed on the SCPU (the SCPU of the previous system is selected here), and finally continue to place it in a constant temperature and humidity test box under the same conditions for curing. After curing is completed, a SOA@SiO2 / SCPU bio-based composite coating is obtained.

[0055] The mechanical properties of the SOA@SiO2 / SCPU bio-based composite coating prepared in the example were tested. Figure 4 The mechanical properties test results of water contact angle of SOA@SiO2 / SCPU bio-based composite coating after different wear treatments, such as Figure 4 As shown in (a), the surface of the SOA@SiO2 / SCPU bio-based composite coating was cyclically rubbed with sandpaper with a weight of 200g, and the superhydrophobicity of the SOA@SiO2 / SCPU bio-based composite coating was maintained within 1.2m without loss; when the contact angle of the coating was less than 150°, SCPU and SOA@SiO2 nanoparticles were repeatedly sprayed, and the water contact angle returned to 160°. The sandpaper abrasion with a weight of 200g was continued, and it was found that the water contact angle of the reconstructed composite all-bio-based coating could be maintained above 150° within 1.2m, which shows that the Si-OCH2CH3 in the silicon SCPU structure has good adhesion to the new and old coatings. Human skin secretes oil, and repeated contact between the superhydrophobic coating and fingers may cause the superhydrophobic performance to fail, such as Figure 4 As shown in (b), after repeatedly rubbing the coating with fingers, it was found that the coating could still maintain its superhydrophobic properties after 160 finger touches. Dynamic impact can also be used as one of the tests of coating tolerance, simulating outdoor rain impact by tap water droplets. The coating was placed 30cm below the tap, and water droplets were controlled to drip onto the coating at a rate of 100mL / min to simulate a rainy scene. The results are shown in Figure 4 As shown in (c), the coating can withstand the impact of water droplets for 180 minutes without losing its superhydrophobic properties. In addition, the spraying process has strong operability for repairing the superhydrophobicity of the coating. After repeated spraying, the coating can restore its superhydrophobic properties, and its mechanical durability is not inferior to that of the coating sprayed for the first time.

[0056] The SOA@SiO2 / SCPU bio-based composite coating prepared in the embodiment was subjected to a chemical stability test. Figure 5 The figure is the test result. It can be seen from the figure that the SOA@SiO2 / SCPU bio-based composite coating has good solvent resistance. Specifically, Figure 5 As shown in (a), the contact angle of the glass sheet coated with SOA@SiO2 / SCPU is still relatively stable (>150°) after being immersed in 3.5% NaCl (simulated seawater) for 120 hours, indicating that the SOA@SiO2 / SCPU bio-based composite coating has strong tolerance to 3.5% NaCl; since both SOA and SCPU contain ester groups, the acidity and alkalinity of the environment have a certain impact on their superhydrophobic properties. The glass sheet was immersed in solutions with different pH values ​​and the water contact angle was tested after 24 hours. The results are shown in Figure 5As shown in (b), it indicates that after being corroded in an acidic solution (pH = 1-7) for 24 hours, the water contact angle of the SOA@SiO2 / SCPU bio-based composite coating is still higher than 150°, maintaining good superhydrophobicity; but in an alkaline solution, the water contact angle of the SOA@SiO2 / SCPU bio-based composite coating decreases rapidly, and the surface wettability undergoes a large change from a superhydrophobic surface to a hydrophilic surface. This property of being superhydrophobic under acidic conditions but converting to superhydrophilic under alkaline conditions has application potential in the field of intelligent conversion of surface wettability.

[0057] The SOA@SiO2 / SCPU bio-based composite coating prepared in the embodiment was subjected to weather resistance test, and the results are as follows Figure 6 As shown in the figure, the SOA@SiO2 / SCPU bio-based composite coating shows good weather resistance. Rainwater, acid rain, tap water and lake water represent four common humidity environments. The static contact angle of SOA@SiO2 / SCPU bio-based composite coating has almost no change under the condition of 120h immersion. The effect of UVA-340 ultraviolet aging lamp (40W) on the super hydrophobicity of SOA@SiO2 / SCPU bio-based composite coating by irradiation simulates the effect of summer noon sunlight. Figure 6 As shown in (a), the water contact angle changes very little within 120 hours. Figure 6 As shown in (b), under different temperature conditions, the SOA@SiO2 / SCPU bio-based composite coating also showed good stability within 24 hours, and the contact angle was greater than 150°. The above tests show that the SOA@SiO2 / SCPU bio-based composite coating has good weather resistance. On the one hand, the excellent weather resistance is related to the enhanced stability of SOA. The unsaturated double bonds on the OA molecular chain react with the thiol group to form saturated long-chain molecules, which enhances its stability. On the other hand, the SCPU resin has good weather resistance to the environment due to its high cross-linking degree and the presence of polysiloxane. Therefore, the superhydrophobic properties of the SOA@SiO2 / SCPU bio-based composite coating show good stability under different environments.

[0058] The SOA@SiO2 / SCPU bio-based composite coating prepared in the embodiment was subjected to a hydrophobicity test. Figure 7 As shown in the figure, the results show that the SOA@SiO2 / SCPU bio-based composite coating has a variety of superhydrophobic properties. Figure 7 As shown in (a), different droplets (soy sauce, vinegar, wine, juice, ink, coffee, milk, tea) on different substrates protected by SOA@SiO2 / SCPU bio-based composite coatings all appear as spherical droplets and are easy to roll freely. Figure 7As shown in (b), the contact angles of the SOA@SiO2 / SCPU bio-based composite coating prepared in this embodiment to common liquid droplets are all greater than 150°, and different substrates do not affect its superhydrophobic effect (the contact angles are all greater than 150°), indicating that the SOA@SiO2 / SCPU bio-based composite coating is suitable for the surfaces of a variety of substrates and has superhydrophobic properties to a variety of common liquids, and has potential application potential in the fields of antifouling and self-cleaning.

[0059] The antifouling performance of the SOA@SiO2 / SCPU bio-based composite coating prepared in the embodiment was tested. Figure 8 The composite bio-based coating has good antifouling properties, such as Figure 8 As shown in (a), a glass sheet is inserted into graphite, soaked for 10 seconds, and taken out and moved to completely away from the sludge water surface as one cycle. It can be clearly observed that the glass sheet in the blank group (without any treatment) is covered with sewage, and it is difficult for sewage droplets to drip; while the surface of the glass sheet coated with the SOA@SiO2 / SCPU bio-based composite coating is dry, and the sewage droplets cannot stop on the coating surface. The cycle is repeated 30 times. The surface of the SOA@SiO2 / SCPU bio-based composite coating has no signs of damage, no sewage droplets, and no water stains on the surface after drying, indicating that the SOA@SiO2 / SCPU bio-based composite coating has a certain degree of durability in its anti-fouling performance against mud. Since graphite particles are easily adsorbed on the surface of the material through van der Waals force, graphite is selected as the pollutant to simulate the scene of gray layer contaminating the glass and investigate the self-cleaning property of the SOA@SiO2 / SCPU coating. Use the hair dryer at the lowest gear to simulate wind blowing, such as Figure 8 As shown in (b), after the graphite powder on the glass sheet of the blank group (without any treatment) was blown off the glass sheet, traces of graphite powder were left at the bottom of the glass sheet, and this trace could not be eliminated by blowing with a hair dryer. However, the graphite powder on the glass coated with the SOA@SiO2 / SCPU bio-based composite coating was quickly blown off the glass sheet almost at the moment of starting up, and there was no stain left on the surface of the glass sheet, indicating that the SOA@SiO2 / SCPU bio-based composite coating can effectively reduce the adsorption of pollutants similar to graphite powder on the surface of objects, and this adsorption can be carried out without liquid infiltration, only by wind blowing off the dust layer, which means that the exterior wall coated with the SOA@SiO2 / SCPU bio-based composite coating prepared in this embodiment can keep the surface clean through air flow in a dry environment, and it is not easy to accumulate dust. In addition, graphite was also used as a pollutant, and water was dripped with a dropper to simulate rainwater to examine the self-cleaning property of the glass sheet coated with the SOA@SiO2 / SCPU bio-based composite coating. Figure 8As shown in (c), the glass sheet is tilted on the petri dish at an angle of about 30°, and graphite particles are sprinkled on the glass sheet. Water is dripped on the coating layer by a rubber-tipped dropper, and the pollutants (graphite powder) on the glass coated with the SOA@SiO2 / SCPU bio-based composite coating roll off with the water drops, gradually restoring a clean surface, presenting an effect similar to the "lotus effect".

[0060] The above verified the hydrophobic properties of the SOA@SiO2 / SCPU bio-based composite coating prepared in this embodiment from various aspects, and the results showed excellent performance.

[0061] The present application is described in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the present application and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing a bio-based super-hydrophobic composite coating, characterized in that: The following steps are involved: S1. Preparation of siloxane-modified castor oil-based polyurethane hybrid solution; S2. Synthetic oleic acid silane coupling agent; S3. The silica was modified with the oleic silane coupling agent obtained in S2 to obtain super-hydrophobic modified silica, and the super-hydrophobic modified silica was added to isopropanol to obtain a super-hydrophobic modified silica solution; S4. Spraying a siloxane-modified castor oil-based polyurethane hybrid solution and a super-hydrophobic modified silica solution on the surface of the substrate in sequence, and obtaining the bio-based super-hydrophobic composite coating after curing.

2. The preparation method according to claim 1, characterized in that: The specific steps of S1 are: (1) adding castor oil, mercaptopropyltrimethoxysilane and a photoinitiator into a sample bottle filled with an inert gas to obtain a first mixture; (2) placing the sample bottle containing the first mixture under ultraviolet light for reaction overnight to obtain silanized castor oil; (3) adding isophorone diisocyanate and castor oil into a sample bottle, and performing a heating reaction under the protection of an inert gas; (4) adding polycaprolactone into the sample bottle to carry out a chain extension reaction to obtain -NCO terminated castor oil-based polyurethane; (5) After cooling, mercaptopropyltrimethoxysilane was added to react, thereby obtaining a uniform and transparent siloxane-modified castor oil-based polyurethane hybrid solution.

3. The preparation method according to claim 2, characterized in that: In step (1), the inert gas is argon, and the photoinitiator is benzoin dimethyl ether, which accounts for 1% to 4% by weight in the first mixture.

4. The preparation method according to claim 2, characterized in that: In step (2), the wavelength of the ultraviolet light is 300-400 nm, and the light intensity is 1200-1500 mW; in step (3), the heating reaction temperature is 60-75° C., and the reaction time is 4-6 h; in step (5), the temperature after cooling is 35-45° C.

5. The preparation method according to claim 1, characterized in that: The specific steps of S2 are: The chemical structure is as follows: The oleic acid shown has the following chemical structure: The 3-mercaptopropylethoxysilane and the photoinitiator shown are mixed to form a second mixture, and the second mixture reacts under ultraviolet light to synthesize a chemical structure as follows: Oleic acid-based silane coupling agent shown.

6. The preparation method according to claim 5, characterized in that: The wavelength of the ultraviolet light is 300-400nm, the light intensity is 1200-1500mW, and the irradiation time is 20-24h; the photoinitiator is benzoin dimethyl ether, and its mass proportion in the second mixture is 1%-4%.

7. The preparation method according to claim 1, characterized in that: The specific steps of S3 are: Silica, anhydrous ethanol and deionized water are mixed and the pH value of the mixed solution is adjusted to 8.5-9.

5. After further ultrasonic treatment, oleic acid silane coupling agent (SOA) is added, mixed evenly, dried, washed with alcohol, and dried again to obtain super-hydrophobic modified silica particles.

8. The preparation method according to claim 1, characterized in that: In S4, the material of the substrate is at least one of glass, metal, wood, concrete, and textile.

9. A bio-based super-hydrophobic composite coating, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bio-based super-hydrophobic composite coating according to claim 9 in the preparation of super-hydrophobic materials and products.